2018
DOI: 10.1107/s2056989018001901
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and Hirshfeld surface analyses of bis[N,N-bis(2-methoxyethyl)dithiocarbamato-κ2S,S′]di-n-butyltin(IV) and [N-(2-methoxyethyl)-N-methyldithiocarbamato-κ2S,S′]triphenyltin(IV)

Abstract: The crystal and molecular structures of the two title organotin dithiocarbamate compounds, [Sn(C4H9)2(C7H14NO2S2)2], (I), and [Sn(C6H5)3(C5H10NOS2)], (II), are described. Both structures feature asymmetrically bound dithiocarbamate ligands leading to a skew-trapezoidal bipyramidal geometry for the metal atom in (I) and a distorted tetrahedral geometry in (II). The complete molecule of (I) is generated by a crystallographic twofold axis (Sn site symmetry 2). In the crystal of (I), molecules self-assemble into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These results gave rise to the suggestion that increasing the length of the alkyl chain leads to enhanced solubility/activity of the compound (Segovia et al, 2002). Complementing these biological investigations (Mohamad, Awang, Kamaludin & Abu Bakar, 2016; are structural studies of organotin dithiocarbamates Mohamad, Awang, Kamaludin, Jotani et al, 2016;Mohamad et al, 2017Mohamad et al, , 2018 and in continuation of the latter, herein, the crystal and molecular structures of (C 6 H 5 ) 3 Sn[S 2 CN(Me)Hex] (I) and (C 6 H 5 ) 3 Sn[S 2 CN(CH 3 )-CH 2 CH 2 Ph] (II) are reported along with a Hirshfeld surface analysis to provide more details on the molecular packing.…”
Section: Chemical Contextmentioning
confidence: 97%
“…These results gave rise to the suggestion that increasing the length of the alkyl chain leads to enhanced solubility/activity of the compound (Segovia et al, 2002). Complementing these biological investigations (Mohamad, Awang, Kamaludin & Abu Bakar, 2016; are structural studies of organotin dithiocarbamates Mohamad, Awang, Kamaludin, Jotani et al, 2016;Mohamad et al, 2017Mohamad et al, , 2018 and in continuation of the latter, herein, the crystal and molecular structures of (C 6 H 5 ) 3 Sn[S 2 CN(Me)Hex] (I) and (C 6 H 5 ) 3 Sn[S 2 CN(CH 3 )-CH 2 CH 2 Ph] (II) are reported along with a Hirshfeld surface analysis to provide more details on the molecular packing.…”
Section: Chemical Contextmentioning
confidence: 97%
“…Two novel organotin(IV) compounds as methoxyethyldithiocarbamate ligands (Scheme 5) were synthesized and characterized in a study by Awang et al (2016). Further determination of the cytotoxic effects of dibutyltin(IV) and diphenyltin(IV) in HL-60 human leukemia cells showed that both compounds had very low IC 50 values (0.40 SCHEME 3 | Chemical structure of 19-20 (Mohamad et al, 2016;Mohamad et al, 2018). SCHEME 4 | Chemical structure of 21-24. and 0.35 μM for compounds 29 and 30, respectively), supporting the strong cytotoxic activities of both compounds.…”
Section: Organotin(iv) Compounds Containing Dithiocarbamate As Ligandsmentioning
confidence: 99%